2022
DOI: 10.3389/fcvm.2022.856600
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Usefulness of Donor-Derived Cell-Free DNA as a Biomarker for Cardiac Allograft Vasculopathy: A Prospective Study

Abstract: BackgroundCardiac allograft vasculopathy (CAV) remains a major cause of morbidity and mortality among long-term heart transplant recipients. There is an unmet need for a non-invasive biomarker of CAV that could obviate the need to perform surveillance coronary angiograms in these patients. Our aim was to evaluate the performance of Donor-derived Cell Free DNA (dd-cfDNA) as a biomarker of CAV.MethodsWe prospectively measured dd-cfDNA levels in all patients undergoing routine coronary angiography >1 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…One small single center study did find an association after 2 years post-heart transplant, where a majority of patients with established CAV had higher levels of dd-cfDNA, compared with a minority of patients without CAV ( 131 ). In contrast, in a Spanish cohort, there was no significant difference in levels of dd-cfDNA comparing heart transplant patients with and without CAV on concurrent angiogram >1 year after transplant ( 132 ). Therefore, the utility of dd-cfDNA to indicate chronic vascular changes within the graft warrants more investigation.…”
Section: Chronic Antibody-mediated Rejection and Transplant Vasculopathymentioning
confidence: 91%
See 1 more Smart Citation
“…One small single center study did find an association after 2 years post-heart transplant, where a majority of patients with established CAV had higher levels of dd-cfDNA, compared with a minority of patients without CAV ( 131 ). In contrast, in a Spanish cohort, there was no significant difference in levels of dd-cfDNA comparing heart transplant patients with and without CAV on concurrent angiogram >1 year after transplant ( 132 ). Therefore, the utility of dd-cfDNA to indicate chronic vascular changes within the graft warrants more investigation.…”
Section: Chronic Antibody-mediated Rejection and Transplant Vasculopathymentioning
confidence: 91%
“…Further, higher levels of dd-cfDNA averaged over the first three months post-transplant conferred a 6.6-fold higher risk of severe CLAD (130). One small single center study did find an association after 2 years postheart transplant, where a majority of patients with established CAV had higher levels of dd-cfDNA, compared with a minority of patients without CAV (131). In contrast, in a Spanish cohort, there was no significant difference in levels of dd-cfDNA comparing heart transplant patients with and without CAV on concurrent angiogram >1 year after transplant (132).…”
Section: Immunologic Risk Factors and Predictive Modelsmentioning
confidence: 99%
“…A small single-center pilot study performed in the US showed that dd-cfDNA is elevated in cardiac allograft vasculopathy (CAV) and suggested endothelial injury and ischemia as possible mechanisms [12]. However, another study from Spain using different dd-cfDNA detection methods and thresholds did not confirm the association between dd-cfDNA and CAV [13].…”
Section: Supporting Evidencementioning
confidence: 99%
“…A small single-center pilot study performed in the US showed that dd-cfDNA is elevated in cardiac allograft vasculopathy (CAV) and suggested endothelial injury and ischemia as possible mechanisms [ 12 ]. However, another study from Spain using different dd-cfDNA detection methods and thresholds did not confirm the association between dd-cfDNA and CAV [ 13 ]. These divergent findings underscore the need for larger prospective studies to define the role of dd-cfDNA in screening for CAV (the SHORE registry is exploring this question).…”
Section: Pico Questions and Recommendationsmentioning
confidence: 99%
“…A single-center study from Madrid, Spain, evaluated dd-cfDNA of 94 recipients at time of angiography and showed no association between dd-cfDNA and presence of CAV. 90 In another study using proteomics, aptamer-based protein expression profiling identified a signature that discriminated patients with mild to moderate CAV, including proteins related to cellular injury, inflammation, and platelet activation. 91 As investigations continue to evaluate molecular methodologies as markers of CAR, it will be important to assess their ability to predict these other posttransplant outcomes.…”
Section: Biomarkers Of Primary Graft Dysfunction and Cardiac Allograf...mentioning
confidence: 99%